Integrasi Praktik Ritual dan Strategi Pertanian pada Tradisi Ruwat Desa di Desa Pidodo Kulon - Sri Puji Lestari; Muhammad Fauzi Syahputra; Rahma Hayati Ikhtiyarani; Nadia Safitri; Miko Andriansyah Ismoko Putro; Salis Nafiyatul Qona`Ah; Muhammad Maghfur Fahrur Rozzi; Luthfiyah Ardiyanti; Irma Istiariyani (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
The Ruwat Desa tradition in Pidodo Kulon has significant spiritual and social importance in maintaining food security and strengthening solidarity among the agrarian community. This study aims to understand how the Ruwat Desa ritual is integrated with agricultural strategies, as well as to examine the role of KKN students in these activities. The method used is descriptive qualitative through observation, interviews, and literature study. The research findings indicate that the community views the Ruwat Desa ritual as a spiritual endeavor that complements technical agricultural efforts, particularly when facing pest threats. The procession of agricultural products is not only a means of expressing gratitude but also strengthens the values of mutual aid and social bonds. The involvement of KKN students adds a dimension of service, as they not only provide technical assistance but also help preserve the continuity of the tradition. Thus, Ruwat Desa serves not only as a cultural heritage but also as a collective strategy for the community to strengthen food security and has the potential to be developed as sustainable cultural tourism.